Leadership in healthcare: a bibliometric analysis of 100 most influential publications. Issue 1 (22nd September 2020) - Bhulani, Nizar; Miao, Timothy L; Norbash, Alexander; Castillo, Mauricio; Khosa, Faisal
Abstract : Aim: We analysed the 100 most influential articles on leadership in healthcare via a bibliometric analysis to better understand categories and topics in leadership science and their relationship to healthcare. Leadership in healthcare is ever evolving and needs to be robust like any another profession. Methods: A bibliometric analysis was performed. Articles were ranked by citation counts and three independent reviewers screened the abstracts for inclusion. Common themes were categorised. Results: Citations for articles ranged from 53 to 487 and were published across 50 journals. Articles focused primarily on three leadership subjects: team building, quality improvement and healthcare delivery. Of healthcare provider groups, articles were directed to or concerning primarily: nursing, academic medicine and critical care medicine. Conclusions: We identified gaps in healthcare leadership development literature. There is an opportunity to effectively identify areas of interest and demand for organised leadership education and training.